Peningkatan Kemampuan Menulis Melalui Metode Bermain Jawaban Dalam Pembelajaran Bahasa Indonesia Kelas III SDN 06 Kampung Baru Pariaman - Ernita Ernita (Jurnal Konseling dan Pendidikan, 2016)
This research is based one fact that the writing skill of student in learning Bahasa was still low.it was caused by method “speech” that teacher used to implement. This research is aimed to improve student’s writing skill by implementing playing-answer method in learning Bahasa. This is class action research whose subject were students grade III in SDN 06 Kampung Baru. Data were obtained through observation sheet and final test. The result shows that average score of students improves from 68.00 inc cycle I to 77.05 in cycle II. Then, percentage of successful students improves from 55% in cycle I to 80% in cycle II. Thus, it can be concluded that implementation of playing-answer method in learning Bahasa can improve student’s writing skill.